LandParcelS: A module for automated land partitioning - Demetriou, Demetris (My University, 2012)
Land fragmentation is a widespread problem and schemes for consolidating land are required to improve agricultural efficiency. This paper explains the development of a module called LandParcelS (Land Parcelling System) that is part of an integrated planning and decision support system called LACONISS which is being developed to assist land consolidation planning in Cyprus. LandParcelS is the component of the system that automates the land partitioning process by optimising land parcels in terms of shape, size and value. The methodology employs a genetic algorithm and results are presented when treating the partitioning task as either a single or multi-objective problem.
Keywords: module; automated land partitioning